A hybrid MCDM model for roles selection in supporting talent development intervention programme in Malaysia public higher education institution - Yau’mee Hayati, Hj Mohamed Yusof; Awanis, Romli (ISTES Organization, 2023)
The process of retaining leadership succession at higher education institutions (HEI) is crucial since it has entailed the process of selecting the ideal candidate. The goal is to guide universities toward maintaining organizations’ excellence for their academic leadership and management (ALM) position. Due to the lack of established standards for assessing the competency of possible successors at their home institutions, many ALM of Malaysia HEIs are difficult to identify the proper replacement for their posts. This study aims to propose a multi criteria tacit knowledge acquisition framework (MC-TKAF) for supporting talent development intervention program in Malaysia HEIs. It will be based on cognitive apprenticeship, socialization and informal learning theory which mostly used in acquiring knowledge from expertise to overcome talent bottleneck among novice. Fuzzy Delphi will be used as the primary methodology in this study to gather agreement regarding the appropriate indicator to measure tacit knowledge competency among ALM at Malaysian HEIs. There are three phases: Phase 1 involves analyzing the current tacit knowledge acquisition (TKA) and identifying the appropriate parameters to build the intended framework. Phase 2 involves using the results of Phase 1 to create a new framework of tacit knowledge acquisition (TKAF) that is appropriate for the HEI environment. Phase 3's final objective is to assess the viability of the Talent Development Intervention Program's (TDIP) Tacit Knowledge Acquisition Framework (TKAF) utilising the Multi Criteria Decision Making (MCDM) approach. This paper's goal is to offer the hybrid MCDM approach as a talent performance indicator for the multi-criteria tacit acquisition framework. The final Phase 3 of the study design will essentially be the subject of this paper. The built-in indicators in this document may be utilised as a guide for the HEI sectors to create talent performance metrics that are appropriate for each TKA applied. © 2023 Published by the ISTES Organization